Transcriptional signature induced by a metastasis‐promoting c‐Src mutant in a human breast cell line. (25th March 2016) - Broecker, Felix; Hardt, Christopher; Herwig, Ralf; Timmermann, Bernd; Kerick, Martin; Wunderlich, Andrea; Schweiger, Michal R.; Borsig, Lubor; Heikenwalder, Mathias; Lehrach, Hans; Moelling, Karin
Abstract : Deletions at the C‐terminus of the proto‐oncogene protein c‐Src kinase are found in the viral oncogene protein v‐Src as well as in some advanced human colon cancers. They are associated with increased kinase activity and cellular invasiveness. Here, we analyzed the mRNA expression signature of a constitutively active C‐terminal mutant of c‐Src, c‐Src(mt), in comparison with its wild‐type protein, c‐Src(wt), in the human non‐transformed breast epithelial cell line MCF‐10A. We demonstrated previously that the mutant altered migratory and metastatic properties. Genome‐wide transcriptome analysis revealed that c‐Src(mt) de‐regulated the expression levels of approximately 430 mRNAs whose gene products are mainly involved in the cellular processes of migration and adhesion, apoptosis and protein synthesis. 82.9% of these genes have previously been linked to cellular migration, while the others play roles in RNA transport and splicing processes, for instance. Consistent with the transcriptome data, cells expressing c‐Src(mt), but not those expressing c‐Src(wt), showed the capacity to metastasize into the lungs of mice in vivo . The mRNA expression profile of c‐Src(mt)‐expressing cells shows significant overlap with that of various primary human tumor samples, possibly reflecting elevated Src activity in some cancerous cells. Expression of c‐Src(mt) led to elevated migratory potential. We used this model system to analyze the transcriptional changes associated with an invasive cellular phenotype. These genes and pathways de‐regulated by c‐Src(mt) may provide suitable biomarkers or targets of therapeutic approaches for metastatic cells. Database: This project was submitted to the National Center for Biotechnology Information BioProject under ID PRJNA288540. The Illumina RNA‐Seq reads are available in the National Center for Biotechnology Information Sequence Read Archive under study ID SRP060008 with accession numbers SRS977414 for MCF‐10A cells, SRS977717 for mock cells, SRS978053 for c‐Src(wt) cells and SRS978046 for c‐Src(mt) cells. Abstract : The proto‐oncogene c‐Src regulates various signaling pathways relevant for cancer and progression to metastasis. A single point mutation at its very C‐terminus, GENL to GENA, that abrogates binding to tumor suppressors promotes c‐Src activity and invasiveness of epithelial cells. Here we compared whole‐genome transcriptomes of human epithelial cells overexpressing either wildtype or mutant c‐Src to reveal the genes and pathways involved in Src‐driven invasiveness.